Factors influencing student perceptions of high-school science laboratory environments - Luketic, Christine D. (2013)
Science laboratory learning has been lauded for decades for its role in fostering positive student attitudes about science and developing students’ interest in science and ability to use equipment. An expanding body of research has demonstrated the significant influence of laboratory environment on student learning. Further research has demonstrated differences in student perceptions based on giftedness. To explore the relationship between giftedness and students’ perceptions of their learning environment, we examined students’ perceptions of their laboratory learning environment in biology courses, including courses designated for high-achieving versus regular-achieving students. In addition, to explore the relationship between students’ perceptions and the extent of their experience with laboratory learning in a particular discipline, we examined students’ perceptions of their laboratory learning environment in first-year biology courses versus elective biology courses that require first-year biology as a prerequisite. We found that students in high-achieving courses had a more favourable perception of all aspects of their learning environment when compared with students in regular courses. In addition, student perceptions of their laboratory appeared to be influenced by the extent of their experience in learning science. Perceptions were consistent amongst regular- and high-achieving students regardless of grade level. In addition, perceptions of students in first year and beyond were consistent regardless of grade level. These findings have critical applications in curriculum development as well as in the classroom. Teachers can use student perceptions of their learning environment to emphasize critical pedagogical approaches and modify other areas that enable enhancement of the science laboratory learning environment.